Exclusive Breastfeeding And Acute Diarrhea In Children: A Cross-Sectional Study - Lukman, Leni; Suryawan, I Wayan Bikin (Medicinus, 2019)
Introduction : Breastmilk is known to contain molecules such as oligosaccharides, sIgA and lactoferrin which hold vital importance in immune system. These molecules specifically functioned to protect the body from pathogens including those causing diarrhea. The objective of this study is to define the relationship between exclusive breastfeeding and acute diarrhea incidence frequency in children as primary outcome and age of first acute diarrhea occurrence in children as secondary outcome.Methods: This is an analytic observational cross-sectional study which included 35 children aged 6-24 months who were admitted to Kaswari Ward Wangaya General Hospital Denpasar between 01 June 2018 to 16 August 2018. Samples were obtained through consecutive sampling method and analyzed data were presented in both tables and narrative.Results: From 35 samples included in this study, 13 were exclusively breastfed (37,1%) and 22 were non-exclusively breastfed (62,9%). Sample characteristics including gender, number of siblings, nutritional status, residence, source of water, age of mother, parent’s occupation and education were comparable between two groups. Total samples who were exclusively breastfed and experience less diarrhea is 13 (p = 0,031; PR = 1,47 CI 95% 1,10-1,95). Total samples who were exclusively breastfed and first age of experiencing diarrhea over 12 months old is 11 (p = 0,002 ; PR = 3,10 CI 95% 1,47-6,27). Conclusion: There is statistically significant relationship between exclusive breastfeeding and acute diarrhea incidence frequency and age of first acute diarrhea occurrence in children aged 6-24 months in Kaswari Ward Wangaya General Hospital.